Intra-luminal thrombus bleeding in abdominal aortic aneurysm as an indicator for acute or impending rupture: A case series - Abdul Rahman, Mohd Norhisham Azmi; Md Ralib @ Md Raghib, Ahmad Razali; Othman, Ahmad Faidzal (The Editorial Committee of Annals of Vascular Diseases, 2016)
Bleeding into Intra luminal thrombus, famously known as “hyper attenuating crescent sign”, due to blood entering the ILT, has been advocated to be associated with impending rupture of abdominal aortic aneurysm (AAA). We present two cases of patients presenting to our centre with a nding as described above. The importance of these nding correlating with intra-operative ndings and review of relevant literatures will be highlighted.